Exploring EFL Students’ Perceptions Toward Language Learning Activities Applied in Indonesian EFL Classroom Today - Ishafiuddin Ismail; Chuzaimah Chuzaimah (Fakultas Sastra - Universitas Muslim Indonesia, 2020)
The present paper sheds light on Indonesian EFL students' perceptions toward learning activities applied in the classroom teaching practice. Classroom activities particularly related to learning activities have been widely accepted as one of factors that influence students’ achievement in learning. In the current study, the researcher attempts to answer three research questions: (1) How important the learning activities in students’ perceptions to facilitate them for learning, (2) what benefits gained from those learning activities? And (3) which learning activities do students perceive to be the most facilitating them in learning? The participants in this study were 21 EFL students, in state university of Makassar. The participant consisted of different term which in the second term, fourth term and sixth term. Survey and open-ended question were developed in collecting data. The researcher analyzed the data through data analysis strategy particularly coding qualitative data. The result of the study analysis showed that the discussion was quite important and both Writing paper/article and Book review were just important, while individual presentation and Quiz were very important activities. Table 3 summarized the students’ perception toward benefits of learning activities. The finding also showed discussion activity to be the most facilitating students in learning.